On the influence of shape and material used for the femoral component pegs in knee prostheses for reducing the problem of aseptic loosening - Bahraminasab, Marjan; Sahari, Barkawi; Edwards, Kevin L.; Farahmand, Farzam; Jahan, Ali; Tang, Sai Hong; Arumugam, Manohar (Elsevier, 2014)
The integration of materials selection and design are essential to the success of new product development, especially when applied to biomedical devices. The knee prosthesis, like any other implant, is a product that still lacks satisfactory design solutions for solving the problem of aseptic loosening. Stress shielding is one of the main causes of aseptic loosening that is intimately related to the overall design of the knee prosthesis. The design of the location pegs in the femoral component of the knee prosthesis is seen to have a critical effect on the stress shielding. In this study, therefore, different combinations of location peg geometries and material designs were assessed using finite element analyses in conjunction with a design of experiments procedure. The materials considered were Co–Cr alloy (as reference material) and functionally graded material (FGM) for the main body of the femoral component, and various porous materials for the pegs (as promising new materials). The performance outputs (responses) were stress levels in the femoral bone to assess the stress shielding effect, and stress levels in the pegs to assess adequate peg strength. The result revealed conflicts in satisfying the design objectives. Therefore, a multi-objective optimization was carried out to find the optimal geometries of the pegs for the femoral component. Based on the findings of the optimization process, a set of candidate designs was generated and a multi-criteria decision making approach used to obtain the final ranking of candidate designs. The ranking order demonstrated the superiority of using a FGM femoral component with porous material pegs of conical geometry. By comparing the results with the standard Co–Cr design, it was shown that the new design of pegs can significantly increase the magnitude of stresses seen at the distal femur; hence reduce the stress shielding effect, without over compromising on the strength of the pegs.